The Effect of Postoperative Korean Traditional Medicine for the of Proximal Humeral Fracture: A Case Report - Hyun Il Go; Hangyul Choi; Jieun Hong; Nam geun Cho (MEDrang Inc., 2019)
The purpose of this case study is to examine the effects of Korean traditional medicine in the postoperative treatment of proximal humeral fracture. The patient with postoperative pain following proximal humeral fracture surgery was treated with Korean traditional medicine including acupuncture cupping therapy and herbal medicine in hospital for 67 days. The effects of the treatment were evaluated using the Numerical Rate Scale (NRS), Range Of Motion (ROM), and Shoulder Pain and Disability Index (SPADI). As a result of treatment, the NRS score was reduced from 7 to 3, the ROM was improved (on average by 21%), SPADI was reduced from 93 to 25.9. This study proposes that Korean traditional medicine may be effective in postoperative treatment for proximal humeral fracture.